2015
DOI: 10.1039/c5fo00467e
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing supports distinct reactive oxygen species-mediated pathways of apoptosis by high and low size mass fractions of Bay leaf (Lauris nobilis) in HT-29 cells

Abstract: DNA double strand breaks mediated by high mass bay leaf fraction in HT-29 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 93 publications
(107 reference statements)
0
6
0
Order By: Relevance
“…26 Similarly, other bioactive compounds from the plants have the ability to arrest the cell cycle at S and G2/M phase in different cancer cell lines. 5,31,35,36 3.6. Effect of MH on cyclin, CDK, p21 waf1/Cip1 and p27 kip1 mRNA expression in HCT-116 and…”
Section: Mh Induces Cell Cycle Arrest Of Hct 116 and Lovo Cellsmentioning
confidence: 99%
“…26 Similarly, other bioactive compounds from the plants have the ability to arrest the cell cycle at S and G2/M phase in different cancer cell lines. 5,31,35,36 3.6. Effect of MH on cyclin, CDK, p21 waf1/Cip1 and p27 kip1 mRNA expression in HCT-116 and…”
Section: Mh Induces Cell Cycle Arrest Of Hct 116 and Lovo Cellsmentioning
confidence: 99%
“…Anticancer: Polar and apolar extracts and essential oil of laurel fruits and leaves present important anticancer activities for various types of cancer, such as leukemia [45,50,52,94,191,[202][203][204], fibrosarcoma [195], neuroblastoma [205][206][207], liver [27], breast [14,27,208], ovarian [39], prostatic [209], colon [27,96,210], colorectal [96], renal [209], skin [211], cervical [27,212], lung [27,213], and intestinal cancer [50].…”
Section: Review On Laurus Nobilismentioning
confidence: 99%
“…These findings are very similar to those of the present study. There is relatively little known about the effect of bay leaf on the cell cycle and apoptosis in CRC cells with the exception of, to the authors’ knowledge, the work of Rodd et al [ 78 ], who reported that unfractionated and low molecular mass fractions of bay leaf were pro-apoptotic (based on caspase-3/7 activity) although their impact varied. In addition, they halted the cell cycle via arrest in the G1/S phase.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding p53, the slight reduction in pro-apoptotic p53 caused by TE was unexpected. However, the HCA-7 cell line has a partially mutated/dysfunctional p53, which in fact can suppress apoptosis [ 78 , 79 ]. Thus, the most likely explanation therefore is that TE simply reduced mutated p53.…”
Section: Discussionmentioning
confidence: 99%